Paradoxical Aesthetics in Panji Mask Visual Structure: Alusan and Gagahan Profiles in Bobung, Yogyakarta - Wijaya, Yasin Surya; Tjahyadi, Sindung; Yulianto, Vissia Ita (Harmonia: Journal of Arts Research and Education, 2022)
This study focuses on Panji masks in Bobung, Yogyakarta region. The study aims to explain the shape, meaning, and paradoxical aesthetic value in the visual form of panji masks focused on alusan and gagahan profiles. A qualitative approach with a multiple-case strategy conducted in the research. Data sources derived from documents/archives, informants, and places/events collected by document analysis techniques, in-depth interviews, and participatory observation. Data validity was tested by data sources triangulation and review informants. Interactive techniques with data reduction procedures, data display, and data verification analyzed data. The results show that the structure of the panji mask in Bobung was composed of visual forms which contained philosophical meanings. The shape and meaning of the Bobung panji masks in Alusan and Gagahan profiles contain an aesthetic value that is dualistic antagonistic (paradoxical). The panji masks in Bobung contain paradoxical aesthetic values in two patterns, three patterns, four patterns, and five patterns. The conclusion is that the visual form of Panji masks in Bobung, Yogyakarta, is structured by paradoxical aesthetic value.